Atmospheric Dynamics Leading to West European Summer Hot Temperatures Since 1851 - M. Carmen Alvarez-Castro; Davide Faranda; Pascal Yiou (Complexity)
Summer hot temperatures have many impacts on health, economy (agriculture, energy, and transports), and ecosystems. In Western Europe, the recent summers of 2003 and 2015 were exceptionally warm. Many studies have shown that the genesis of the major heat events of the last decades was linked to anticyclonic atmospheric circulation and to spring precipitation deficit in Southern Europe. Such results were obtained for the second part of the 20th century and projections into the 21st century. In this paper, we challenge this vision by investigating the earlier part of the 20th century from an ensemble of 20CR reanalyses. We propose an innovative description of Western-European heat events applying the dynamical system theory. We argue that the atmospheric circulation patterns leading to the most intense heat events have changed during the last century. We also show that the increasing temperature trend during major heatwaves is encountered during episodes of Scandinavian Blocking, while other circulation patterns do not yield temperature trends during extremes.